2014
DOI: 10.1007/978-94-017-9487-9_5
|View full text |Cite
|
Sign up to set email alerts
|

Th17 Differentiation and Their Pro-inflammation Function

Abstract: CD4(+) T helper cells are classical but constantly reinterpreted T-cell subset, playing critical roles in a diverse range of inflammatory responses or diseases. Depending on the cytokines they release and the immune responses they mediate, CD4(+) T cells are classically divided into two major cell populations: Th1 and Th2 cells. However, recent studies challenged this Th1/Th2 paradigm by discovering several T-helper cell subsets with specific differentiation program and functions, including Th17 cells, Treg ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 338 publications
(465 reference statements)
1
44
0
1
Order By: Relevance
“…Th17 cells and their typical cytokine, IL-17, were functionally characterized as tissue inflammatory modulator [31]. It was demonstrated that neutrophil activation and tissue damage were reduced in IL-17 deficient animals and the increased level of IL-17 was related to the pathogenesis of various parasites [3236].…”
Section: Discussionmentioning
confidence: 99%
“…Th17 cells and their typical cytokine, IL-17, were functionally characterized as tissue inflammatory modulator [31]. It was demonstrated that neutrophil activation and tissue damage were reduced in IL-17 deficient animals and the increased level of IL-17 was related to the pathogenesis of various parasites [3236].…”
Section: Discussionmentioning
confidence: 99%
“…Th17 cells secreted IL‐17A which is the signature cytokine. IL‐17A holds a distinct pro‐inflammatory effect …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, IL‐17‐secreting T cells appear to present a relatively heterogeneous population. Typically, Th17 cells produce IL‐17, IL‐21 and IL‐22 . However, IL‐6 or IFN‐ γ , and even IL‐10, can be produced by IL‐17‐secreting CD4 + T cells .…”
Section: Discussionmentioning
confidence: 99%